2010
DOI: 10.4028/www.scientific.net/amm.43.78
|View full text |Cite
|
Sign up to set email alerts
|

Type Synthesis and Workspace Analysis of a Novel Series Chinese Medical Massage Arm

Abstract: Based on the Chinese medical massage manipulation of rolling, pressing, kneading and pushing, the serial mechanical arm with six rotational joints and the end actuator with 3-DOF parallel mechanism are selected, and a new type of hybrid massage robot is proposed. The type synthesis of this massage arm is designed from two aspects, the arm and the wrist. 6R serial joint massage arm is adopted. Using Denavit-Hartenberg coordinate system, the kinematics model of this massage robot is established and the direct ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Around the theme of rehabilitation massage, many researchers in China, America, Japan and further afield have carried out many research programmes and several massage robots have been reported (Yin and Xu, 2010;Xie and Kuang, 2010;Alavandar et al, 2007). The PUMA robot was used in the application of robotics in massage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Around the theme of rehabilitation massage, many researchers in China, America, Japan and further afield have carried out many research programmes and several massage robots have been reported (Yin and Xu, 2010;Xie and Kuang, 2010;Alavandar et al, 2007). The PUMA robot was used in the application of robotics in massage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the main ways in the design and optimization processes of robots [2]. Based on graphical approach, Xie Jun et al [3] analyzed the workspace of a novel series Chinese medical massage arm, and learned that the upper arm and the forearm of this kind of Chinese medical massage arm must be equal. Chen Zaili [4] presented a genetic algorithm approach for the synthesis of spatial 6-DOF parallel manipulators whose workspace must include a desired workspace with orienting capabilities on a given 3D region.…”
Section: Introductionmentioning
confidence: 99%